2020
DOI: 10.1002/jcb.29474
|View full text |Cite
|
Sign up to set email alerts
|

The lncRNA SNHG15/miR‐18a‐5p axis promotes cell proliferation in ovarian cancer through activating Akt/mTOR signaling pathway

Abstract: Here, we report the expression pattern, function and regulatory mechanism of SNHG15 together with miR-18a-5p micro RNA in ovarian cancer (OC) for the first time. We recruited 20 patients and took normal ovarian tissues and ovarian tumor tissues from them. We used cell culture, transfection, in vivo tumor xenograft assay, and multiple types of detection assays to investigate the expression and regulation of long noncoding RNA (lncRNA) SNHG15/miR-18a-5p in ovarian tissues and cells. Results: We found that the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 33 publications
(70 reference statements)
3
8
0
Order By: Relevance
“…Subsequently, SNHG15 was investigated in tumor, and the SNHG15 expression was upregulated in cancers and high SNHG15 expression predicted poor prognosis, for instance, gastric cancer [ 17 ], lung cancer [ 18 ], colorectal cancer [ 29 ], and glioma [ 24 ]. Consistent with the recent evidence raised by Zhang et al [ 30 ], our results showed that SNHG15 was upregulated in ovarian cancer; it is noteworthy that our results were based on the GEO dataset and verified by the specimen of our own; this makes the results more reliable. In addition, the prognostic role of SNHG15 was identified by Kaplan-Meier plotter database due to our limited sample size and SNHG15 was correlated with poor PFS.…”
Section: Discussionsupporting
confidence: 92%
“…Subsequently, SNHG15 was investigated in tumor, and the SNHG15 expression was upregulated in cancers and high SNHG15 expression predicted poor prognosis, for instance, gastric cancer [ 17 ], lung cancer [ 18 ], colorectal cancer [ 29 ], and glioma [ 24 ]. Consistent with the recent evidence raised by Zhang et al [ 30 ], our results showed that SNHG15 was upregulated in ovarian cancer; it is noteworthy that our results were based on the GEO dataset and verified by the specimen of our own; this makes the results more reliable. In addition, the prognostic role of SNHG15 was identified by Kaplan-Meier plotter database due to our limited sample size and SNHG15 was correlated with poor PFS.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, OC patients with low miR-18a-5p expression presented short survival. Consistently, miR-18a-5p is reported to be downregulated in OC cells and tissues [ 36 ]. miR-18a exerts repressive roles in OC cells, whose low expression is linked with the poor prognosis and malignant phenotype of OC patients [ 50 ].…”
Section: Discussionmentioning
confidence: 66%
“…miR-18a-5p is abundant in embryonic stem cell-derived small EVs [ 53 ]. miR-18a mimic could relieve OC cell migration and invasion [ 36 ]. Taken together, hMSC-EVs inhibited OC cell proliferation, migration, and invasion by carrying miR-18a-5p.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SNHG15 is an lncRNA which plays critical roles in the development and progression of various cancers through regulation of Akt/mTOR signaling [153,154]. It has been reported as a prognostic marker in colorectal and liver cancers [155,156].…”
Section: Snhg15mentioning
confidence: 99%